1988
DOI: 10.1139/v88-397
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer complexation of N,N-dimethyl-p-toluidine with nitrogen heteroaromatic cations as a model for association complexes in hydride transfer reactions

Abstract: Can. J. Chem. 66, 2532. Charge-transfer complexation of N,N-dimethyl-p-toluidine (DMT) with each of the following N-methyl cations has been investigated in acetonitrile solution at 25OC: acridinium; phenanthridinium; 3-X-quinolinium and 4-X-isoquinolinium (X = H, Br, CONH2, CN); 5-nitroisoquinolinium; 3-X-pyridinium (X = CONH2, CN) (also the N-benzyl pyridinium cations); N,N1-dimethyl-4,4'-dipyridylium dication. Charge-transfer absorption maxima are reported, and extinction coefficients ( E , , , ) at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Using the Benesi–Hildebrands method, 63 we estimate the equilibrium constant K DA to be 0.96 M –1 . When applied to the conditions used in the spectroscopic analysis of Figure 4 b, an additional 0.3 μM 9 + · can be accounted for as originating from a donor–acceptor complex.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Using the Benesi–Hildebrands method, 63 we estimate the equilibrium constant K DA to be 0.96 M –1 . When applied to the conditions used in the spectroscopic analysis of Figure 4 b, an additional 0.3 μM 9 + · can be accounted for as originating from a donor–acceptor complex.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In fact a weak charge-transfer complex has been shown (19) to be formed immediately upon mixing 1-benzyl-1,4-dihydronicotinamide and the lo-methylacridinium cation, with the rate of disappearance of this complex being identical to the rate of hydride transfer between these two species. A fuller exploration of the association of neutral aromatic species with the various heteroaromatic cations of this study is reported in the accompanying paper (52).…”
Section: Discussionmentioning
confidence: 99%
“…other workers have also concluded that such charge-transfer species may lie on the reaction coordinate for these formal hydride transfer processes (3,30). It should be noted that it has been established (32)(33)(34) that the order of charge-transfer absorption maxima (A,,,) with a common donor species follows the order: xanthylium > tropylium > 10-methylacridinium > 1-methylquinolinium > ' l,5-Dihydro-3,10-dimethyl-5-deazaisoalloxazine …”
mentioning
confidence: 95%